Advancing governance indicator systems: Lessons learned from the 2022 symposium - Helmut K. Anheier; Regina A. List; Edward L. Knudsen (Global Policy, 2023)
The Berggruen Governance Index (BGI) is a new and innovative entry into the crowded domain of quantitative governance research. In its effort to contribute to the field, the BGI builds off of and acts in dialogue with several other governance indicator projects from across the globe. As part of a collaborative outlook, the BGI convened the first of three symposia at the UCLA Luskin School in October 2022, titled `Advancing Governance Indicator Systems: The 2022 Conference'. The event invited representatives from other indicator projects to share their thoughts on the BGI, present their own projects and discuss avenues for further research and development of `planetary' indicators. This article discusses the highlights and key contributions from the conference.
Keywords: 320